Pengelolaan Potensi Desa oleh Badan Usaha Milik Desa Sangatta Utara Sejahtera di Desa Sangatta Utara Kabupaten Kutai Timur: Management of Village Potentials by Village-Owned Company of North Sangatta Village, Kutai Timur District - Faradhilla Andriyani (JOURNAL OF GOVERNMENT SCIENCE, 2020)
This study describes and analyzes the management of village potentials by the Village-Owned Enterprises of Sangatta Utara Sejahtera (BUMDESUS) of Sangata Utara Village and its impact to the community. This qualitative descriptive research uses purposive sampling and the data collection was carried out through participant observation, in-depth interviews, and documentary research. Findings show that there are three village potentials, namely Taman Bersemi (Village Park), Kenyamukan Beach, and BUMDesmart (village-owned enterprise). However, only Village Park and BUMDesmart can be managed. Kenyamukan Beach is unable to be managed properly as this asset  belongs to three authorities: Sangata Utara Village of Kutai Timur Regency, Kutai Regency Government, and the Provincial Government of East Kalimantan. The management of village potentials by BUMDESUS has two impacts, namely economic impact that can be seen from an increase in village revenues and livelihood source of local community; and the impact on community-based residential development.  Keywords: management, village potentials, village owned enterprise